2014
DOI: 10.1002/ijc.29312
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear bile acid receptor FXR controls the liver derived tumor suppressor histidine‐rich glycoprotein

Abstract: The nuclear bile acid receptor Farnesoid X receptor (FXR) is strongly expressed in liver and intestine, controls bile acid and lipid homeostasis and exerts tumor-protective functions in liver and intestine. Histidine-rich glycoprotein (HRG) is an abundant plasma protein produced by the liver with the proposed function as a pattern recognition molecule involved in the clearance of immune complexes, necrotic cells and pathogens, the modulation of angiogenesis, the normalization of deranged endothelial vessel str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…A likely explanation is that hepatic BA uptake by transporters like sodium/taurocholate cotransporting polypeptide NTCP is rapidly reduced by hepatic FXR activation. 5,6 In contrast, when 0.5 mg/kg Px-102 was given to humans for 7 days, serum levels of BAs decreased, 12 and similar findings were reported following 7 days of treatment with modified FGF19, 11 underscoring the different response patterns following acute and chronic treatment.…”
Section: Impactsupporting
confidence: 59%
“…A likely explanation is that hepatic BA uptake by transporters like sodium/taurocholate cotransporting polypeptide NTCP is rapidly reduced by hepatic FXR activation. 5,6 In contrast, when 0.5 mg/kg Px-102 was given to humans for 7 days, serum levels of BAs decreased, 12 and similar findings were reported following 7 days of treatment with modified FGF19, 11 underscoring the different response patterns following acute and chronic treatment.…”
Section: Impactsupporting
confidence: 59%
“…Administration of A. ilicifolius extract reverted the activity of LDH to near normal in drug-treated animals may be due to the inhibition of glycolysis and render the protection to the membrane. Carbohydrate moieties of glycoprotein have been implicated in the transport of metabolites across cell membranes and also a direct relation between glycoproteins and tumor genesis is observed (Deuschle et al, 2015). In the present study, the levels of glycoproteins hexose, hexosamine and sialic acids were significantly increased in DEN induced cancer bearing animals.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, we observed a strong correlation between DNA methylation and HRG mRNA expression using the cBio cancer genomics portal ( Figure S6 B) 34 . Previous studies had found that HRG was a transcriptional target gene of nuclear bile acid receptor Farnesoid X receptor (FXR) in liver cells 35 . NF-κB binds to FXR and subsequently suppresses its transcriptional activity, leading to the downregulation of FXR downstream genes 36 , 37 .…”
Section: Resultsmentioning
confidence: 99%